Australian Sports Commission Annual Report 2022-23 (Australian Sports Commission, 2024)
This report has been prepared in accordance with parliamentary reporting and legislative requirements and provides details of the ASC`s performance and operations for the financial year ending 30 June 2023. The report details how effective the ASC has been at achieving its outcomes for the year as outlined in the ASC Corporate Plan 2022-26 and the Portfolio Budget Statements for 2022-23.